A MINI REVIEW ON ZINGIBERACEAE FAMILY AS ANTIDIABETIC PLANTS: ACTIVE INGREDIENTS AND MECHANISMS OF ACTIONS - Fatiya Zata Ishmah; Agus Sulaeman (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion. Therapy using conventional anti-diabetic drugs is associated with serious side effects, and herbs to maintain chronic disease if conventional drugs not adequate. The purpose of this article review is to find out information about plants of the Zingiberaceae family that have anti-diabetic activity with the mechanism of action of ? -glucosidase enzyme inhibition, ? -amylase enzyme inhibition, and increased GLP-1 levels. The sources used consisted of 27 journals and reviewed 9 research journals originating from Google Scholar, Pubmed, NCBI, Elsevier, Science Direct with a span of under 10 years. The articles were then analyzed using the systematic literature review method, by collecting, evaluating, and developing research on a particular topic. From several studies conducted, the results showed that plants from the family that have antidiabetic activity include Zingiber officinale (ginger), Curcuma longa (turmeric rhizome), Curcuma aeruginosa (temu hitam), Curcuma zanthorrhiza (curcuma), Zingiber cassumunar (bangle), Kaempferia galanga (kencur), Alpinia galanga (lengkuas), Etlingera elatior (kecombrang, honje), and Elettaria cardamomum (kapulaga). Keywords: Antidiabetic; Diabetes Mellitus;Â Zingiberaceae